Why Not Home?: A Study of the Impact of an Effort to Reduce Postacute Expenditures. Issue 1 (January 2022) - Chovanec, Kelli A.; Arsene, Camelia; Beck, Amanda; Liedel, Bethany
Abstract : Purpose of Study: Accountable Care Organizations (ACOs) aiming to reduce healthcare expenditure adopt strategies targeting costly postacute service utilization, asking "why not home?" as a part of the hospital discharge planning paradigm. This study examined the impact of an interventional approach to implement evidence-based interventions to improve transitions of care to the least restrictive next site of care on the rate of skilled nursing facility (SNF) admissions per 1, 000, SNF length of stay (LOS), and total SNF cost. Primary Practice Setting: The impact of the interventional approach for an ACO-attributed Medicare population, analyzing Medicare Shared Savings Plan Part A and Part B beneficiary claims data, was examined. Methodology and Sample: A pre-/postintervention analysis was conducted, for dates of service 12 months pre- and postintervention for patients admitted to any hospital within the integrated health care system. The outcome variables were defined as SNF admission rate, SNF LOS, cost of care (total SNF cost, SNF cost per admission), and hospital LOS prior to SNF discharge. Results: There was early evidence of the effectiveness of the multifaceted interventions that involved the delivery of interprofessional team member education focused on the tenets of value-based care and discharging patients to the least restrictive setting, as appropriate. In the normalized data review, it was noted that the rate of SNF discharges per 1, 000 patients changed from 73 per 1, 000 patients in the preintervention period to 70 per 1, 000 patients in the postintervention period. The total SNF cost in the postintervention period only increased by 3%, with a difference of 616, 014, despite the 10% increase in the total ACO-attributed patient population during the same period. Implications for Case Management Practice: The results of this study imply that a multifaceted intervention with aims to shift the transitional care planning paradigm toward discharging to the least restrictive next site of care is an effective strategy for ACOs with aspirations to improve the utilization and expenditure in the postacute setting. The analyses suggest that providing education to interprofessional team members that reinforces the tenets of value-based care and the importance of asking, "why not home?" for every hospitalized patient, and leveraging technology-based insights positively impact discharge rates to SNF and other ACO outcomes.